FRI0358 USAGE OF C-REACTIVE PROTEIN TESTING IN THE DIAGNOSIS AND MONITORING OF PSORIATIC ARTHRITIS (PSA): RESULTS FROM A REAL-WORLD SURVEY IN THE US AND EUROPE. (2nd June 2020) - Ogdie, A.; Tillett, W.; Eder, L.; Booth, N.; Bruce Wirta, S.; Howell, O.; Schubert, A.; Peterson, S.; Chakravarty, S. D.; Coates, L. C.
Abstract : Background: C-reactive protein (CRP) is an important non-specific marker of both acute and chronic inflammation and can be elevated in patients with PsA. The role of CRP in the management of PsA is unclear. Objectives: To describe how CRP testing is implemented in real-world clinical practice for disease management of PsA. Methods: A cross-sectional study among patients with PsA recruited by rheumatologists and dermatologists was conducted in France, Germany, Italy, Spain, UK and US. Data were collected from Jun-Aug 2018 via physician-completed patient record forms. Use of CRP testing was obtained by asking the physician to state (yes/no) whether CRP was used to aid PsA diagnosis, confirm the patient's PsA and to monitor the patient's PsA. Where physicians stated use of CRP testing, they were then asked to provide the number of CRP tests conducted in the last 12 months. Results: Data were collected for 2270 patients with PsA (595 US, 1675 EU5). In EU5, 78.7% of patients had CRP conducted to aid diagnosis (vs 43.4% in US) and 72.0% had CRP conducted to monitor their condition (vs 34.6% in US). Patients seen by rheumatologists (vs dermatologists) were at least 50% more likely to have CRP used for monitoring purposes, this difference being most pronounced in the US. In EU5, CRP was conducted a mean [SD] of 2.7 [1.7] times in the last 12 months, versus 2.0 [1.4] in the US. Country level usage of CRP testing is shown in Table 2 . Conclusion: The majority (80.9%) of patients with PsA in EU5 had at least one CRP test in the last 12 months, versus 42.9% in the US. CRP is more commonly used for diagnosis and monitoring of PsA in Europe compared to the US and is more commonly ordered by rheumatologists than dermatologists. Disclosure of Interests: Alexis Ogdie Grant/research support from: Pfizer to Penn, Novartis to Penn, Amgen to Forward/NDB, Consultant of: Abbvie, Amgen, Bristol-Myers Squibb, Celgene, Corrona, Janssen, Eli Lilly, Novartis, Pfizer, William Tillett Grant/research support from: AbbVie, Celgene, Eli Lilly, Janssen, Novartis, Pfizer Inc, UCB, Consultant of: AbbVie, Amgen, Celgene, Lilly, Janssen, Novartis, MSD, Pfizer Inc, UCB, Speakers bureau: AbbVie, Amgen, Celgene, Lilly, Janssen, Novartis, Pfizer Inc, UCB, Lihi Eder Grant/research support from: Abbvie, Lily, Janssen, Amgen, Novartis, Consultant of: Janssen, Speakers bureau: Abbvie, Lily, Janssen, Amgen, Novartis, Nicola Booth Consultant of: Janssen, Sara Bruce Wirta Employee of: Janssen-Cilag Sweden AB, Oliver Howell Employee of: Janssen, Agata Schubert Employee of: Janssen-Cilag, Steve Peterson Employee of: Janssen Research & Development, LLC, Soumya D Chakravarty Shareholder of: Johnson & Johnson, Employee of: Janssen Scientific Affairs, LLC, Laura C Coates: None declared